Brief Report: Contralateral Lobectomy for Second Primary NSCLC: Perioperative and Long-Term Outcomes - Jennie K. Choe, MD; Amy Zhu, BS; Alexander J. Byun, MD; Junting Zheng, MS; Kay See Tan, PhD; Joe Dycoco, BS; Manjit S. Bains, MD; Matthew J. Bott, MD; Robert J. Downey, MD; James Huang, MD; James M. Isbell, MD; Daniela Molena, MD; et al. (JTO Clinical and Research Reports, 2022)
Introduction: Anatomical resection—often by lobectomy—is the standard of care for patients with early stage NSCLC. With increased diagnosis, survival, and prevalence of persons with early stage NSCLC, the incidence of second primary NSCLC, and consequently, the need for contralateral lobectomy for a metachronous cancer, is increasing. Perioperative outcomes after contralateral lobectomy are unknown. Methods: Among patients who underwent contralateral lobectomy for second primary NSCLC during 1995 to 2020, we evaluated 90-day mortality and major morbidity (Clavien-Dindo grades 3–5) rates and their association with clinicopathologic variables, including the year of contralateral lobectomy and duration between lobectomies. Results: A total of 98 patients underwent contralateral lobectomy for second primary NSCLC; 51 during an early time period (1995–2009) and 47 from a late time period (2010–2020). There were five mortalities and 23 patients with major morbidities after contralateral lobectomy; both rates decreased in 2010 to 2020 compared with 1995 to 2009 (mortality 10%–0%, major morbidity 35%–11%). Major morbidity was associated with an interval of less than 1 year between lobectomies, a diffusing capacity of the lung for carbon monoxide <80%, and right lower lobe resections. Mortality was associated with squamous cell carcinoma. Patients who underwent contralateral lobectomy for stage I NSCLC had 74% (95% confidence interval: 64%–85%) 3-year overall survival and 15% (95% confidence interval: 6.5%–24%) 3-year lung cancer cumulative incidence of death. Conclusions: Contralateral lobectomy for second primary early stage NSCLC was associated with poor outcomes before 2010. Since 2010, perioperative and long-term outcomes of contralateral lobectomy have been comparable with reported outcomes after unilateral lobectomy.